Preparation method of lithium aluminum titanium phosphate solid electrolyte powder
Lithium titanium aluminum phosphate solid electrolyte powder was prepared by combining low-temperature liquid phase method with solid phase calcination method, which solved the problems of stability of liquid electrolyte in lithium-ion battery and high energy consumption and lithium loss of traditional preparation methods, and achieved improved high ionic conductivity and electrochemical stability.
Patent Information
- Application Number
- CN202511130603.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-13
- Publication Date
- 2025-11-07
AI Technical Summary
Existing liquid electrolytes for lithium-ion batteries suffer from thermal instability, poor ion selectivity, and low electrochemical stability. Furthermore, traditional preparation methods result in lithium loss, high energy consumption, complex processes, and low ionic conductivity.
A method combining low-temperature liquid-phase method and solid-phase calcination method was adopted to generate pure crystalline phase of lithium titanium aluminum phosphate at low temperature, and then calcination at a lower temperature to eliminate crystal defects and improve lattice integrity, thereby preparing lithium titanium aluminum phosphate solid electrolyte powder.
High ionic conductivity of lithium titanium aluminum phosphate solid electrolyte powder was achieved, which simplified the process, reduced energy consumption, avoided lithium loss, and improved the electrochemical stability and ionic conductivity of the material.
Smart Images

Figure CN120903460A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The application belongs to the technical field of solid-state battery materials, and particularly relates to a preparation method of lithium aluminum titanium phosphate solid-state electrolyte powder. BACKGROUND
[0002] The rapid rise of lithium ion batteries not only reshaped the huge market of portable electronic devices (mobile phones, smart watches, notebook computers, etc.) and promoted the efficient use of clean energy, but also helped the actual commercialization process of electric vehicles (EVs), further alleviating the environmental crisis caused by high dependence on fossil fuels and serious carbon dioxide emissions. Therefore, lithium batteries are indispensable in many fields, including portable electronic devices, electric vehicles, and large-scale stationary energy storage. The mainstream lithium ion battery still cannot meet the strict requirements of safety and extreme use conditions due to the use of a large amount of organic electrolyte. Although liquid electrolytes have high ionic conductivity and excellent electrode surface wetting advantages, they often have serious thermal instability, poor ion selectivity, and low electrochemical stability. Therefore, it is an urgent need to develop lithium ion batteries with higher safety, high energy density, long cycle life, and low cost. Replacing liquid electrolytes with solid-state electrolytes can fundamentally solve these safety problems.
[0003] NASICON-type LiTi2(PO4)3 has become a very promising solid-state electrolyte due to its high chemical / thermal stability, good ionic conductivity, and extremely low raw material cost. Although LTP grains exhibit high Li -4 conductivity of 10 + S / cm, its total ionic conductivity at room temperature is only 10 -8 ~ 10 -6 S / cm, which is due to the high resistance of the low-density grain boundary phase. Researchers Aono et al. pointed out that the ionic conductivity of solid-state electrolytes increases with the increase of the tap density of sintered tablets. Specifically, the structure of LTP crystals can be modified by trivalent atomic heteroatom doping to prepare high-density ceramic materials. Al 3+ Doping agents not only enhance the bonding strength of Ti-O bonds, but also weaken Li-O bonds in the microstructure, thereby improving ionic conductivity. Many researchers found that among different Li 1+x Al x Ti 2-x (PO4)3 (LATP) derivatives, Li 1.3 Al 0.3 Ti 1.7 (PO4)3 has the highest Li + conductivity.
[0004] The researchers have carried out more researches on the preparation and application of the LATP electrolyte powder, and the synthesis of the solid electrolyte powder is very important because the powder with high pure phase content is the premise of sintering high ionic conductivity ceramics. The preparation methods of the LATP powder mainly include solid phase sintering method, liquid phase coprecipitation method and sol-gel method, wherein the solid phase sintering method is simple in process, but the sintering temperature is above 1000 DEG C, so that the lithium salt is lost due to volatilization at high temperature, and in addition, the energy consumption is also relatively high; the coprecipitation method is difficult to control the hydrolysis rate of titanium salt in the material preparation process, and it is difficult to control the morphology, and the subsequent sintering temperature is high; the sol-gel method has mild synthesis conditions and low calcination temperature, but the raw material cost is high, and the process is relatively complex, and the lithium ion conductivity of the products obtained by the above methods is not ideal. SUMMARY
[0005] In view of the problems of the prior art, the present application provides a preparation method of lithium aluminum titanium phosphate solid electrolyte powder, which combines low-temperature liquid phase method and solid phase calcination method. First, lithium aluminum titanium phosphate pure crystal phase is generated at a relatively low temperature, and then the crystal defects are eliminated by solid phase calcination at a relatively low temperature to improve the lattice integrity and thus improve the ionic conductivity of the material. The problems of the prior art, such as high synthesis temperature, easy loss of lithium, high energy consumption, complex process and low ionic conductivity, are solved.
[0006] To achieve the above object, the following technical scheme is adopted in the present application.
[0007] A preparation method of lithium aluminum titanium phosphate solid electrolyte powder, which is prepared by the chemical formula Li 1+x Al x Ti 2-x (PO4)3, wherein 0.3≤x≤0.5, and the method comprises the following steps:
[0008] S1, weighing lithium source, aluminum source, titanium dioxide and phosphorus source according to the molar ratio of (1+x):x:(2-x):3-3.3 of Li, Al, Ti and P;
[0009] S2, dissolving the lithium source, the aluminum source and the phosphorus source in deionized water, adding sulfuric acid with a molar concentration of 0.01-0.02 mol / L to adjust the pH value to less than 7, forming an acidic precursor mixed solution, and the pH value is preferably 2-4;
[0010] S3, adding titanium dioxide powder and organic solvent to the hydrothermal reaction kettle, the volume ratio of the organic solvent to the deionized water is 1:1 to 1:3, and the titanium dioxide is fully dispersed by continuous stirring;
[0011] S4, the precursor mixture in step S2 is added to the reactor in step S3, and a hydrothermal reaction is carried out at a temperature in the range of 190 DEG C to 230 DEG C to obtain a hydrothermal precursor slurry;
[0012] S5, the hydrothermal precursor slurry obtained in step S4 is subjected to suction filtration and washing, and then dried at a temperature in the range of 80 DEG C to 120 DEG C to obtain an intermediate product powder;
[0013] S6, the powder obtained in step S5 is calcined at a temperature in the range of 600 DEG C to 725 DEG C to obtain a final lithium titanium aluminum phosphate powder.
[0014] Preferably, the lithium source comprises one or more combinations of lithium hydroxide, lithium carbonate, lithium sulfate, lithium nitrate, lithium chloride or lithium acetate.
[0015] Preferably, the aluminum source comprises one or more combinations of aluminum nitrate, aluminum sulfate or aluminum chloride.
[0016] Preferably, the phosphorus source compound comprises one or more combinations of phosphoric acid, di-ammonium hydrogen phosphate or mono-ammonium hydrogen phosphate.
[0017] Preferably, the titanium dioxide powder is one of rutile type, anatase type or a mixture of rutile and anatase.
[0018] Preferably, the organic solvent in step S3 comprises one of ethylene glycol, polyethylene glycol 200 to 1000, diethylene glycol or propylene glycol.
[0019] Preferably, in step S5, after the hydrothermal precursor slurry is subjected to suction filtration, it is first washed three times with deionized water, then washed three times with alcohol, and then dried at a temperature in the range of 80 DEG C to 120 DEG C.
[0020] Preferably, the calcination time in step S5 is in the range of 4 hours to 8 hours.
[0021] Preferably, the hydrothermal reaction time in step S4 is in the range of 12 hours to 24 hours.
[0022] Compared with the prior art, the present application has the following beneficial effects:
[0023] 1. The present application provides a lithium titanium aluminum phosphate solid-state electrolyte powder and a preparation method thereof, which is prepared by a two-step method. First, a lithium titanium aluminum phosphate pure crystal phase is prepared by a low-temperature liquid phase method. Then, the crystal defects in the lithium titanium aluminum phosphate prepared by the low-temperature liquid phase method are eliminated by calcination at a relatively low temperature of 600 DEG C to 725 DEG C through a solid phase method, so as to improve the lattice integrity and finally improve the ionic conductivity of the material.
[0024] 2. Direct synthesis of lithium titanium aluminum phosphate crystals at low temperature: The present application uses a specific solvent thermal reaction condition in an acidic environment to successfully achieve the direct synthesis of Li 1+x Al x Ti 2-x (PO4)3(0.3≤x≤0.5) solid electrolyte crystals, avoiding the dependence of traditional high-temperature solid phase or multi-step calcination route on crystal formation, simplifying the process flow.
[0025] 3. Improve the reactivity of titanium dioxide and promote the formation of complete crystal phase: By adjusting the pH of the solution to be acidic, the dissolution of the poorly soluble TiO2 powder is effectively promoted, thereby improving the uniform co-precipitation and crystal growth behavior of Al, Ti, P and other components, and inhibiting the generation of heterogeneous phases caused by non-uniform reaction.
[0026] 4. Avoid the resolubilization of the main crystal phase under acidic conditions: The present application introduces an organic solvent (such as ethylene glycol) mixed with deionized water in a certain volume ratio, which can enhance the reactivity of TiO2 in an acidic environment and buffer the system acidity, thereby preventing the resolubilization of the lithium titanium aluminum phosphate main crystal phase in the later reaction, improving the purity and crystallinity of the product phase.
[0027] 5. Form a single-phase NASICON structure with high ionic conductivity: By optimizing the solvothermal conditions and subsequent calcination treatment, the obtained solid electrolyte powder presents a single NASICON crystal structure, XRD test shows no obvious impurity peaks, the particle size is controlled in the range of 100 nm to 800 nm, and has excellent room temperature ionic conductivity (10 -4 ~ 10 -3 S / cm) and high specific surface area, which helps to improve the electrolyte / electrode interface contact and lithium ion migration performance.
[0028] 6. Calcination for defect regulation rather than crystal phase formation: Unlike the "calcination to promote crystal phase formation" in the prior art, the calcination in the present application is only used to further remove organic residues and regulate the defect concentration of the crystal, and the main crystal phase has been formed in the solvothermal process, showing the efficiency and directionality of the process. BRIEF DESCRIPTION OF DRAWINGS
[0029] In order to more clearly illustrate the specific embodiments of the present application or the technical solutions in the prior art, the following will briefly introduce the drawings needed to be used in the specific embodiments or prior art description. Obviously, the drawings described below are some embodiments of the present application, and those skilled in the art can also obtain other drawings according to these drawings without creative labor.
[0030] FIG. 1 XRD of lithium titanium aluminum phosphate powder in Example 1. DETAILED DESCRIPTION
[0031] The following description is presented to enable any person skilled in the art to practice the application as claimed. The preferred embodiments disclosed herein are only examples of the application and alternative variations could be adopted by one skilled in the art without departing from the spirit and scope of the application.
[0032] Embodiment 1, the chemical formula of the lithium titanium aluminum phosphate solid electrolyte powder of this embodiment is Li 1.3 Al 0.3 Ti 1.7 (PO4)3, and the specific preparation method is as follows:
[0033] Step 1, lithium hydroxide, aluminum sulfate, rutile titanium dioxide and phosphoric acid are weighed according to the molar ratio of Li, Al, Ti and P as 1.3:0.3:1.7:3.1.
[0034] Step 2, the lithium hydroxide, aluminum sulfate and phosphoric acid are fully dissolved in deionized water to make the concentration of phosphoric acid in the solution 6 mol / L, and a certain amount of sulfuric acid is added to form an acidic precursor mixed solution with a pH of 2, wherein the molar concentration of sulfuric acid is 0.02 mol / L.
[0035] Step 3, add titanium dioxide powder and organic solvent ethylene glycol to the hydrothermal reactor, wherein the volume ratio of ethylene glycol to deionized water is 1:2, and continue to stir for 30 min to make the titanium dioxide fully dispersed.
[0036] Step 4, add the mixed solution of Step 2 to the reactor and react at 200℃ for 12h to obtain a hydrothermal precursor slurry.
[0037] Step 5, after washing the slurry obtained in Step 4 with deionized water and alcohol, dry it at 120℃ to obtain an intermediate product powder; finally, calcine the dried powder at 725℃ in air atmosphere for 8h to obtain the final lithium titanium aluminum phosphate electrolyte powder.
[0038] FIG. 1 DETAILED DESCRIPTION FIG. 1 The XRD pattern of the lithium titanium aluminum phosphate powder in Example 1 is shown, which shows a single NASICON phase structure without obvious impurity peaks; the particle size distribution is 120nm-650nm; the conductivity at room temperature is 2.7x10⁻ 4 S / cm, and the specific surface area is about 612 m² / g, which meets the performance requirements of high ion conduction and good interface contact of solid electrolyte in lithium batteries.
[0039] Embodiment 2, the chemical formula of the lithium titanium aluminum phosphate solid electrolyte powder of this embodiment is Li 1.3 Al 0.3 Ti 1.7 (PO4)3, and the specific preparation method is as follows:
[0040] First step, according to the molar ratio of Li, Al, Ti, P 1.3:0.3:1.7:3, lithium hydroxide, aluminum sulfate, rutile titanium dioxide, phosphoric acid.
[0041] Second step, dissolve lithium hydroxide, aluminum sulfate and phosphoric acid in deionized water, make the concentration of phosphoric acid in the solution 3mol / L, then add a certain amount of sulfuric acid to form an acidic precursor mixed solution, PH is 3, the molar concentration of sulfuric acid is 0.01mol / L.
[0042] Third step, add titanium dioxide powder and organic solvent ethylene glycol to the hydrothermal reaction kettle, the volume ratio of ethylene glycol and deionized water is 1:1, and continue to stir for 30min to make the titanium dioxide fully dispersed.
[0043] Fourth step, add the mixed solution of the second step to the reaction kettle, react at 230℃ for 12h to obtain hydrothermal precursor slurry.
[0044] Fifth step, after washing the slurry obtained in the fourth step with deionized water and alcohol, dry it at 80℃, and finally calcine the dried powder at 700℃ in air atmosphere for 5h to obtain the final lithium aluminum titanium phosphate electrolyte powder.
[0045] Example 3, the chemical formula of the lithium aluminum titanium phosphate solid electrolyte powder of this embodiment is Li 1.5 Al 0.5 Ti 1.5 (PO4)3, the specific preparation method is:
[0046] First step, according to the molar ratio of Li, Al, Ti, P 1.5:0.5:1.5:3.3, lithium sulfate, aluminum sulfate, anatase titanium dioxide and phosphoric acid are weighed.
[0047] Second step, dissolve lithium sulfate, aluminum sulfate and phosphoric acid in deionized water, make the concentration of phosphoric acid in the solution 3mol / L, then add a certain amount of sulfuric acid to form an acidic precursor mixed solution, PH is 2, the molar concentration of sulfuric acid is 0.01mol / L.
[0048] Third step, add titanium dioxide powder and organic solvent diethylene glycol to the hydrothermal reaction kettle, the volume ratio of diethylene glycol and deionized water is 1:1, and continue to stir for 30min to make the titanium dioxide fully dispersed;
[0049] Fourth step, add the mixed solution of the second step to the reaction kettle, react at 190℃ for 24h to obtain hydrothermal precursor slurry.
[0050] Fifth step, after washing the slurry obtained in the fourth step with deionized water and alcohol, dry it at 80℃, and finally calcine the dried powder at 600℃ in air atmosphere for 8h to obtain the final lithium aluminum titanium phosphate electrolyte powder.
[0051] Example 4, the lithium aluminum titanium phosphate solid electrolyte powder of this embodiment has a chemical formula of Li 1.3 Al 0.3 Ti 1.7 (PO4)3, and the specific preparation method is as follows:
[0052] First step, according to the molar ratio of Li, Al, Ti, P 1.3:0.3:1.7:3.3, lithium carbonate, aluminum sulfate, anatase titanium dioxide and phosphoric acid are weighed.
[0053] Second step, dissolve lithium carbonate, aluminum sulfate and phosphoric acid in deionized water, so that the concentration of phosphoric acid in the solution is 6 mol / L, then add a certain amount of sulfuric acid to form an acidic precursor mixed solution, the PH is 4, and the molar concentration of sulfuric acid is 0.02 mol / L.
[0054] Third step, add titanium dioxide powder and organic solvent diethylene glycol to the hydrothermal reaction kettle, the volume ratio of ethylene glycol to deionized water is 1:1, and continue to stir for 30 min to make the titanium dioxide fully dispersed;
[0055] Fourth step, add the mixed solution of the second step to the reaction kettle, and react at 190℃ for 24h to obtain a hydrothermal precursor slurry.
[0056] Fifth step, after the slurry obtained in the fourth step is washed with deionized water and alcohol, it is dried at 80℃, and finally the dried powder is calcined at 700℃ in air atmosphere for 4h to obtain the final lithium aluminum titanium phosphate electrolyte powder.
[0057] The above shows and describes the basic principles, main features and advantages of the present application. It should be understood by those skilled in the art that the present application is not limited to the above examples, and the above examples and descriptions in the specification are only the principles of the present application. Without departing from the spirit and scope of the present application, various changes and improvements can be made to the present application, and these changes and improvements all fall within the scope of the claimed present application.
Claims
1. A method for preparing a lithium titanium aluminum phosphate solid-state electrolyte powder, characterized by: A solid state electrolyte of the formula Li 1+ x Al x Ti 2-x (PO4)3, where 0.3 < x < 0.5, comprising the steps of: S1, weighing lithium source, aluminum source, titanium dioxide and phosphorus source according to the molar ratio of Li, Al, Ti, P (1+x):x:(2-x):3~3.3; S2, dissolving the lithium source, aluminum source and phosphorus source in deionized water, adding sulfuric acid with a molar concentration of 0.01~0.02 mol / L to adjust the pH value to 2-4, forming an acidic precursor mixed solution; S3, adding titanium dioxide powder and organic solvent to the hydrothermal reaction kettle, the volume ratio of organic solvent to deionized water is 1:1 to 1:3, and the titanium dioxide is fully dispersed by continuous stirring; S4, adding the precursor mixed solution in step S2 to the reaction kettle in step S3, and performing hydrothermal reaction at 190℃ to 230℃ to obtain a hydrothermal precursor slurry; S5, the hydrothermal precursor slurry obtained in step S4 is subjected to suction filtration and washing, and then dried at 80℃~120℃ to obtain an intermediate product powder; S6, the powder obtained in step S5 is calcined at 600℃~725℃ to obtain the final titanium aluminum lithium phosphate powder.
2. The method of claim 1, wherein the lithium titanium aluminum phosphate solid-state electrolyte powder is prepared by the steps of: preparing a lithium titanium aluminum phosphate precursor solution; and drying the lithium titanium aluminum phosphate precursor solution to obtain the lithium titanium aluminum phosphate solid-state electrolyte powder. The organic solvent in step S3 includes one of ethylene glycol, polyethylene glycol 200 to 1000, diethylene glycol or propylene glycol.
3. The method of claim 1, wherein the lithium titanium aluminum phosphate solid-state electrolyte powder is prepared by the steps of: preparing a lithium titanium aluminum phosphate precursor solution; and drying the lithium titanium aluminum phosphate precursor solution to obtain the lithium titanium aluminum phosphate solid-state electrolyte powder. The lithium source includes one or more combinations of lithium hydroxide, lithium carbonate, lithium sulfate, lithium nitrate, lithium chloride or lithium acetate.
4. The method of claim 1, wherein the lithium titanium aluminum phosphate solid-state electrolyte powder is prepared by the steps of: preparing a lithium titanium aluminum phosphate precursor solution; and drying the lithium titanium aluminum phosphate precursor solution to obtain the lithium titanium aluminum phosphate solid-state electrolyte powder. The aluminum source includes one or more combinations of aluminum nitrate, aluminum sulfate or aluminum chloride.
5. The method of claim 1, wherein the method further comprises: The phosphorus source compound includes one or more combinations of phosphoric acid, diaminium hydrogen phosphate or ammonium dihydrogen phosphate. 6. The method of claim 1, wherein the lithium titanium aluminum phosphate solid-state electrolyte powder is prepared by the steps of: mixing a lithium source, a titanium source, an aluminum source, and a phosphate source to form a mixture; and heating the mixture to form the lithium titanium aluminum phosphate solid-state electrolyte powder. The titanium dioxide powder is one of rutile type, anatase type or a mixture of rutile and anatase.
7. The method of claim 1, wherein the lithium titanium aluminum phosphate solid-state electrolyte powder is prepared by the steps of: mixing a lithium source, a titanium source, an aluminum source, and a phosphate source; and sintering the mixture at a temperature of 600-900 °C for 1-10 hours in an inert atmosphere. In step S5, after suction filtration of the hydrothermal precursor slurry, the hydrothermal precursor slurry is washed with deionized water three times, then washed with alcohol three times, and then dried at 80℃ to 120℃.
8. The method of claim 1, wherein the lithium titanium aluminum phosphate solid-state electrolyte powder is prepared by the steps of: mixing a lithium source, a titanium source, an aluminum source, and a phosphate source; and calcining the mixture at a temperature of 600-900 °C for 1-10 hours in an inert atmosphere. The calcination time in step S5 is 4 hours to 8 hours.
9. The method of claim 1, wherein the lithium titanium aluminum phosphate solid-state electrolyte powder is prepared by the steps of: mixing a lithium source, a titanium source, an aluminum source, and a phosphate source; and calcining the mixture at a temperature of 600-900 °C for 1-10 hours in an inert atmosphere. The hydrothermal reaction time in step S4 is 12h~24h.